Structural and Computational-Driven Molecule Design in Drug Discovery (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue aimed to provide deep mechanistic insights into strategies in structural dynamics studies and computational methods. The areas of research included but were not limited to the following: structural dynamics studies, computer-aided drug designs, molecular dynamic simulations, molecular docking, virtual screening, QSAR, and in silico ADMET analyses.